(untitled) (Bangladesh Journal of Microbiology, 2010)
Different parts of various plants or their extracts have been used to treat a number of diseases from the ancient time due to their therapeutic value. However, their mechanism of actions remains mostly undiscovered. In this study, brine shrimp (Artemia salina) lethality and antibacterial activity of Azadirachta indica and Terminalia arjuna ethanolic leaf extracts were investigated. A. indica extract showed greater brine shrimp cytotoxicity with lethal concentration 50 (LC50) value of 36.813 mg/ml, whereas the LC50 value of T. arjuna extract was 44.157 mg/ml. Antimicrobial activity of these extracts was assayed by agar-well diffusion method and it was found that both of the extracts were effective against both Gram-positive and Gram-negative bacteria. Later, we found that the cellular proteins isolated from Shigella dysenteriae, which were treated with both of the plant extracts, were aggregated. This aggregation of proteins was demonstrated by detection of protein bands at the upper portion of both of the stacking and separating gels. The extracts-mediated aggregation of cellular proteins might be responsible for the cytotoxic effect that ultimately caused death of the bacterial cells. All of the above results suggest that both of the plant extracts have potential bioactivities that may have therapeutic value. These findings may lead us to develop new effective medicine in future. Key words: Azadirachta indica; Terminalia arjuna; Brine shrimp; Antibacterial activity; Protein aggregation DOI: http://dx.doi.org/10.3329/bjm.v25i2.4873 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 115-121